Feasibility Study of Podo Town Square Gemek Pedestrian, Kedungwuni District, Pekalongan Regency - Aris Krisdiyanto; Kemmala Dewi; Archi Rafferti Kriswandanu; Althea Serafim Kriswandaru; M. Makhfud Riyadi (Ridwan Institute, 2022)
The Institute of Technology and Science (ITS) campus, Pusmanu Polytechnic, SMA Negeri 1 Kedungwuni, SMK Negeri 1 Kedungwuni, SMP Negeri 2 Kedungwuni as an educational center, There are shophouses along the right and left side of the road as a trading place. This is the reason why so many people come to the area. So in the Podo-Surabaya segment, human movement in the area is high. The more visitors who come to the place will impact the concentration of pedestrians. With a large pedestrian flow and the presence of street vendors and illegal parking at several points along the sidewalk, it will significantly affect the comfort and flexibility of pedestrians. For this reason, it is necessary to plan for improving pedestrian facilities in the area. To obtain the minimum width, the required sidewalk width, and pedestrian facilities are calculated according to the Technical Guidelines no. 032/T/BM/1999 “Guidelines for Planning Pedestrian Paths on Public Roads, Minister of Public Works Decree No. 468/KPTS/1998